Global landscape on exploitative leadership: a bilbiometric analysis - Jimbun, Joanna Loura; Mohamed, Rosmah; Bali Mahomed, Anuar Shah; Subramaniam, Anusuiya (Faculty of Education, University of Malaya, 2022)
This study examines the current dynamic exploitative leadership studies and proposes a direction for future research of the field. A bibliometric approach was applied to observe 87 samples of documents from the Scopus database to identify research activity on exploitative leadership. We presented the initial stage of the research in exploitative leadership, the subsequent trends, publications status based on the source title and country. This study uses Microsoft Excel to conduct frequency analysis, VOSviewer for data visualization, and Harzing's Publish or Perish for metrics and analysis citation. The result depicts that exploitative leadership may enter a growth phase in the future. Developing countries exhibited an increase in the momentum, creating a distance with their comrades with a justifiable gap. The studies on exploitative leadership had been cited 13 times by 13 documents, indicating 13 h-index. Meanwhile, 19 g-index shows that the top 19 documents have been cited 361 times. The top three productive authors were Akhtar, Husnain, and Kashif from Pakistan and are known to be the first contributors to the study of exploitative leadership. The keywords in this study also contribute to the discovery of future research. The relevance of this study started from the inadequacy of exploitative leadership and there were limited studies on the negative effect of exploitative leadership as a predictor. There were also limited studies on the application of bibliometric analysis of exploitative leadership. Thus, this study fulfils the gap to investigate the exploitative leadership research trends and discuss the implications for theory and research.